Ethnobotanical Study (Identification, Medical Properties and How to Use) of some Medicinal Plants of Behbahan city of Khuzestan Province, Iran - Damoun Razmjoue; Zahra Zarei; Raham armand (Institue of Medicinal Plants, ACECR, 2017)
Background: The ethnobotanical science to study how the people of a race, culture or specific area use the native plants of that region. Since the methods and the indications of medicinal plants in the different regions are various. Objective: The present study was conducted with the purpose of introducing the traditional application of medicinal plants of Behbahan City for curing the diseases. Methods: For this purpose, after gathering the native plants of region simultaneously, the local name, medicinal properties, How to use and the other information related to the species were gathered. Results: In this study, 60 plant species belong to 23 families were identified. The Lamiaceae, Apiaceae, Asteraceae, Poaceae and Solanaceae families respectively with having 7, 7, 6, 5 and 4 species had the most number of plants species. By examining the types of plants used as Sodden consumption was found that most (45%) and then the tail and Crude (30 percent). Conclusion: Existence of 60 medicinal plant species in Behbahan City shows that the city is reach in terms of having access to medicinal plants; and this matter can provide suitable field for better usage of medicinal plants of this city for producing the productions with more effectiveness and less disadvantages.